Georgia Public Expenditure and Financial Accountability Performance Assessment Report : City of Tbilisi - World Bank (World Bank, Washington, DC, 2018)
The purpose of this Public Expenditure and Financial Accountability (PEFA) assessment is to provide an objective analysis of the present performance of the PFM system in the City of Tbilisi against the PEFA indicators. This PEFA provides an update of progress in PFM in the municipality since the last PEFA in 2014 and establishes a new PEFA baseline using the 2016 PEFA methodology. The assessment covered expenditures by subnational government budgetary units. Revenues are collected by the Georgia Revenue Services on behalf of the municipality and this was considered not applicable. There are no extra-budgetary units and no local government below the municipality level. Overall, the results of the PEFA show that public financial management systems in the City of Tbilisi are strong and improved as the PFM Reform Action Plan has been implemented. The aggregate expenditure side of the budget performs largely according to plan. There is an impressive array of information regarding the finances of the municipality. As a result, the budget documents include most of the basic, and much of the supplementary information, required to support a transparent budget process. Information on performance plans and achievements in service delivery outputs and outcomes across the sectors under the municipality is very good. However, a strategic selection process is lacking in managing the public investment program although monitoring and reporting of implementation is sound. Good progress has been made towards a comprehensive medium-term expenditure framework based on a program budgeting for results approach. There is an effective budget calendar although the issuance of ceilings could be made timelier. The legislature has sufficient time to carry out its scrutiny function.